ANALISIS PEMBERDAYAAN USAHA KECIL MENENGAH PENGHASIL PRODUK BERBAHAN BAKU SAGU DI DESA BANGLAS KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Arief Rifa'i H; Hendry Andry (VALUTA, 2016)
This study analyzes the theme of empowerment of small and medium enterprises producing productsmade from sago in the Village District of Tebing Tinggi vast Meranti Islands regency in Riau province.Sago contain carbohydrates and may be an alternative to the staple food rice paddy fields began todecrease, or as food additives other than rice. This means that the potential of sago as an alternative torice big enough. During this time the production of sago sago farmers and SMEs in the District Merantiintended to meet local market and surrounding areas as well as sold to various regions in Indonesia,including the export opportunities are not limited to the countries neighboring Malaysia but also to othercountries. Research on sago as a staple food alternatives is urgent. With the reason that most people donot properly understand the uses and benefits of corn as the raw material processed foods. As a result,the cultivation of sago is not optimized because the market demand is still small. This study aims toidentify the potential of SMEs producing products made from sago didesa vast Tebing Tinggi District ofMeranti Islands regency, efforts to diversify the food products made from sago results micro-entrepreneurs or SMEs to be more diverse. Includes also examined the potential development of themarket to make it more comprehensive, and the efforts - efforts to empower sago entrepreneurs throughbusiness and production management system better by the Department of Industry, Trade, MerantiIslands District Koperasidan SMEs through capital assistance, support equipment and training.